Tinjauan Kebijakan Kesehatan Mental di Indonesia: Menuju Pencapaian Sustainable Development Goals dan Universal Health Coverage - Khoirunnisa Ghefira Yusrani; Nurul Aini; Shifa Aulia Maghfiroh; Novita Dwi Istanti (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Mental health is a harmony in life that is created between the functions of the soul and the ability to overcome problems. Mental health policies are still limited and not yet integrated. Indonesia is also committed to achieving SDGs and UHC. The purpose of this research is to review mental health policies in Indonesia and evaluate the extent to which these policies support the achievement of the SDGs and UHC. This study uses a literature study to examine different methods. The article search strategy uses an online database, namely Google Scholar and this research uses a literature review methodology. There is a need for comprehensive mental health services to be made part of the SDGs and UHC. The government continues to pursue various mental health policies in order to reduce the prevalence of mental disorders in Indonesia. However, several mental health programs that have been prepared still have deficiencies in the implementation process. The lack of availability of psychotropic drugs at the puskesmas and the existence of a report format that is not yet uniform and the presence of mental health recording and reporting officers are obstacles in the practice of mental health policy in Indonesia. Therefore, sufficient quality data is needed to formulate effective policies so that efforts to deal with mental health at the primary and secondary health service levels are far more optimal. So that continuous improvement can be carried out to reduce the prevalence of mental disorders in Indonesia.